Exploring the experiences of black graduates in accessing employment in South Africa - Leokaoke, Malesitsi (Department of Social Development, 2025)
This research explores the experience of unemployment amongst black graduates in Cape Town, South Africa. The aim of the study was to examine how young black people navigate their way in life when they have graduated with a degree but are unable to find employment. The study sought to understand their educational choices and experiences, the challenges of being a young black graduate and yet still unemployed, and possible ways to improve employment prospects among this cohort. Taking a qualitative approach and a phenomenological research design, the researcher conducted face-to-face and telephonic interviews with twelve unemployed young people who had graduated from a tertiary institution in South Africa and were selected through purposive and snowball sampling techniques. The goal was to uncover how graduate unemployment affects South African youth and whether the problem of unemployment lies with the subject (or other) choices of the youth or the hostile labour market. The research took a qualitative data analysis procedure. Through thematic analysis patterns, statements and the experiences of the participants were collected and analysed to gain more understanding. The goal was to understand how the level of graduate unemployment might be reduced. The findings of the study reveal that there is a clear mismatch between the qualifications of graduates and the qualifications that the South African labour market demands. This has led to many young people being unable to find work despite their possession of a higher education qualification. It was also found that, regardless of the suitability or unsuitability of their qualifications for the labour market, participants were disadvantaged by their lack of knowledge, skills and practical ability to respond to available employment opportunities. Career guidance, which, arguably, is a crucial element in facilitating synergy between education and employment, was noticeably missing for most of the participants. In addition, they lacked the work experience so often required to secure employment. To address these circumstances, it is recommended that career guidance be taken seriously from the early schooling stages. In addition, the offering of internships should be made compulsory for companies, so that inexperienced undergraduates may gain some valuable work experience before they qualify. The findings reveal that most of the participants recognised their need for experience in order to succeed in the labour market. The complexities of the market are highlighted as a contributor to the increase in graduate unemployment.